2016
DOI: 10.1074/jbc.m115.698456
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Signaling Underlies Fast Repetitive Plasma Membrane Translocation of Conventional and Novel Protein Kinase C Isoforms in β Cells

Abstract: PKC signaling has been implicated in the regulation of many cell functions, including metabolism, cell death, proliferation, and secretion. Activation of conventional and novel PKC isoforms is associated with their Ca2+- and/or diacylglycerol (DAG)-dependent translocation to the plasma membrane. In β cells, exocytosis of insulin granules evokes brief (<10 s) local DAG elevations (“spiking”) at the plasma membrane because of autocrine activation of P2Y1 purinoceptors by ATP co-released with insulin. Using total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Additionally our approach revealed that ATP triggers the activity of PKC kinase. This observation is in agreement with the current hypothesis proposing that ATP promotes insulin exocytosis partly by raising calcium concentration and partly by increasing DAG via PLC pathway4445. These results illustrate how unbiased MS-based phosphoproteomics can be applied to identify molecular targets involved in known outcomes as well as those involved in as yet uncharacterized effect of the drugs.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally our approach revealed that ATP triggers the activity of PKC kinase. This observation is in agreement with the current hypothesis proposing that ATP promotes insulin exocytosis partly by raising calcium concentration and partly by increasing DAG via PLC pathway4445. These results illustrate how unbiased MS-based phosphoproteomics can be applied to identify molecular targets involved in known outcomes as well as those involved in as yet uncharacterized effect of the drugs.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that this manipulation activates a completely different set of downstream DAG effector proteins. It has, for example, recently been shown that different PKC isoforms can decode Ca 2+ and DAG changes differently in β cells (25), so the magnitude, synchronization, and duration of these second messenger signals will control downstream signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…Two mutations in the SMP domain of GFP‐opto—E‐Syt1 were generated by site‐directed mutagenesis using the following primers: for L308W, 5′‐GCTGCCTTCCTCGTGTTGCCCAACCGATGGCTGGTGCCCC‐3′ and rev 5′‐CGACGGAAGGAGCACAACGGGTTGGCTACCGACCACGGGG‐3′; for V169W, 5′‐GCTTCTGGCTGAAACTGTGGCTCCGGCTTGGAGGGGATCTA‐3′ and rev 5′‐CGAAGACCGACTTTGACACCGAGGCCGAACCTCCCCTAGAT‐3′ (12) (Q5 Site‐Directed Mutagenesis Kit; New England Biolabs, Ipswich, MA, USA). Infra‐red fluorescent protein (iRFP)‐tandem C2‐domains of PKC (C1aC1b) C1aC1b was generated by replacing GFP with iRFP (24) in the previously described GFP‐C1aC1b (25). All salts, cyclopiazonic acid, carbamoylcholine, and diazoxide were from MilliporeSigma (Burlington, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis suggests that some IP3 is generated locally, whereas the biosensor assay we use in this study can detect only changes in global PIP2. Imaging techniques such as total internal reflection fluorescence (Wuttke et al, 2016) and a knockdown of potentially relevant signaling components can test these ideas in the future.…”
Section: Discussionmentioning
confidence: 99%